The efficacy of telemedicine for pain management in patients with cancer: a systematic review and meta-analysis - Wenyu Chen; Jie Huang; Zhifang Cui; Lei Wang; Liang Dong; Weifeng Ying; Ye Zhang (SAGE Publishing, 2023)
Background: Pain is the most common cancer-related symptom, but it is often undertreated. Telemedicine is widely used in cancer treatment, but its effectiveness is uncertain. Objective: We aimed to evaluate the impact of telemedicine intervention on pain in patients with cancer. Design: Methodological quality and risk-of-bias evaluation were conducted, and the sources of heterogeneity were explored through subgroup analysis and sensitivity analysis. Data Sources and Methods: PubMed, Embase, Web of Science, Cochrane Library, and clinical trial databases were searched up to 16 August 2022. Randomized controlled trials of the impact of telemedicine intervention regarding pain in patients with cancer were included, and the results related to pain were extracted. Results: Twenty-one randomized controlled trials were selected from 1810 articles. A total of 1454 patients received telemedicine interventions, and 2213 received conventional medical services. Telemedical intervention had a positive effect on improving pain intensity [standard mean deviation (SMD) = −0.28, 95% confidence interval (CI): −0.49 to −0.06, p  = 0.01] and pain interference (SMD = −0.41, 95% CI: −0.54 to −0.28, p  < 0.00001), with statistical difference between the two groups. The subgroup analysis results showed that the telemedicine subgroup based on an application (SMD = −0.54, 95% CI: −0.91 to −0.18, p  = 0.004) and the subgroup with intervention time ⩾ 6 months (SMD = −0.33, 95% CI: −0.52 to −0.13, p  = 0.001), both demonstrated significant improvement regarding pain intensity, with significant statistical difference between the two groups. When the follow-up time was ⩾ 6 months, there was no significant difference (SMD = −0.24, 95% CI: −0.55 to 0.07, p  = 0.13). Conclusion: Compared with conventional medical services, telemedicine intervention can improve the pain of patients with cancer and is effective and acceptable regarding symptom monitoring. Integrating telemedicine interventions into cancer pain management may be a feasible option. But its long-term effects still need to be confirmed with more high-quality randomized controlled trials in the future. Registration: https://www.crd.york.ac.uk/PROSPERO/ ; CRD42022361990